2006
DOI: 10.1245/s10434-006-9049-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Biomarkers of Oxidative Stress and Inflammation in Patients with Hepatitis C Virus-Associated Hepatocellular Carcinoma

Abstract: Background: This study evaluated the relationship between inflammation, intra-hepatic oxidative stress, oxidative DNA damage and the progression of liver carcinogenesis in hepatitis C virus (HCV)-infected humans.Methods: Non-cancerous liver tissues were collected from 30 patients with an HCV-associated solitary hepatocellular carcinoma (HCC) who received curative tumor removal. After surgery, the patients were followed at monthly intervals at the outpatient clinic. Distribution of the inflammatory cells (CD68+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 30 publications
0
88
0
Order By: Relevance
“…Previous studies have suggested that oxidative stress induced by increased ROS and/or impairment of antioxidant mechanism is one of the reasons for hepatocellular damage in chronic infections [38][39][40][41][42] and might be associated with the development of HCC [9]. It has also been suggested that oxidative stress biomarkers could potentially be used as a useful clinical diagnostic tool to predict the duration of survival in patients with HCVassociated HCC [43]. Since patients with greater intrahepatic oxidative stress are associated with increase risk of HCC, the present study looked at the potential role of antioxidant defense system enzymes as a useful clinical diagnostic tool in predicting the duration of disease in patients with chronic hepatitis-associated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that oxidative stress induced by increased ROS and/or impairment of antioxidant mechanism is one of the reasons for hepatocellular damage in chronic infections [38][39][40][41][42] and might be associated with the development of HCC [9]. It has also been suggested that oxidative stress biomarkers could potentially be used as a useful clinical diagnostic tool to predict the duration of survival in patients with HCVassociated HCC [43]. Since patients with greater intrahepatic oxidative stress are associated with increase risk of HCC, the present study looked at the potential role of antioxidant defense system enzymes as a useful clinical diagnostic tool in predicting the duration of disease in patients with chronic hepatitis-associated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the group of patients with hepatic 8-OHdG counts exceeding 75 positive cells per 10 5 mm 2 , the HCC incidence during the first 3 years was extremely high (38.8%) ( Figure 3A), indicating that these patients constitute a very high-risk subgroup for developing HCC and should necessarily be carefully monitored by several modalities. Recently, Maki et al (2007) evaluated the expression levels of 8-OHdG of non-cancerous hepatic tissues in HCV-infected patients who developed HCC and received curative tumour resection. The postoperative cumulative HCC-free survival was significantly shorter in patients with the highest percentage of 8-OHdG-positive hepatocytes, indicating that the hepatic 8-OHdG levels are also useful for prediction of HCC recurrence in patients with chronic HCV infection who developed HCC.…”
Section: Discussionmentioning
confidence: 99%
“…4-HNE was reported to be a good biomarker for predicting disease-free survival in patients with HCC and CH-C; however, a weaker association with disease outcome when compared to 8-OHdG was noted (36). maki et al reported high expression of 4-hnE in livers with ch-c and hcc compared to controls (36), while in another study, 4-hnE protein adducts were detected in only a few hepatocytes in livers with CH-C (37). The expression level of 4-hnE protein adducts in livers with ch-B was found to be lower than that in livers with CH-C (38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that high expression of 8-OHdG in livers with CH-C predicted the development of primary hcc (33,34) and also postoperative recurrence (35,36), suggesting the association of 8-OHdG and carcinogenesis in livers with CH-C. However, the expression levels of 8-OHdG in the livers of Group N were low, suggesting that abundant expression of 8-OHdG is not essential for developing HCC.…”
Section: Discussionmentioning
confidence: 99%